2012
DOI: 10.1155/2012/397389
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Prenatal Protein Restriction onβ-Adrenergic Signalling of the Adult Rat Heart during Ischaemia Reperfusion

Abstract: A maternal low-protein diet (MLP) fed during pregnancy leads to hypertension in adult rat offspring. Hypertension is a major risk factor for ischaemic heart disease. This study examined the capacity of hearts from MLP-exposed offspring to recover from myocardial ischaemia-reperfusion (IR) and related this to cardiac expression of β-adrenergic receptors (β-AR) and their associated G proteins. Pregnant rats were fed control (CON) or MLP diets (n = 12 each group) throughout pregnancy. When aged 6 months, hearts f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
1
6
1
Order By: Relevance
“…This sex-specific effect is consistent with findings in rats in which IUGR, as a result of either hypoxia or low protein diet, caused cardiac remodeling and impaired recovery to ischemia-reperfusion in adult male offspring, but had no effect on the female heart [47]. It has also been shown that female rats exposed to chronic prenatal hypoxia exhibited an improved contractility and increased coronary flow with respect to male rats [48,56]. Moreover, human studies showed that IUGR children tend to keep their relatively smaller left cardiac structures in adulthood.…”
Section: Cardiovascular Changessupporting
confidence: 89%
“…This sex-specific effect is consistent with findings in rats in which IUGR, as a result of either hypoxia or low protein diet, caused cardiac remodeling and impaired recovery to ischemia-reperfusion in adult male offspring, but had no effect on the female heart [47]. It has also been shown that female rats exposed to chronic prenatal hypoxia exhibited an improved contractility and increased coronary flow with respect to male rats [48,56]. Moreover, human studies showed that IUGR children tend to keep their relatively smaller left cardiac structures in adulthood.…”
Section: Cardiovascular Changessupporting
confidence: 89%
“…In addition, recent work indicates that prenatal exposure to hypoxia or cocaine inhibit the infarct-sparing effects of ischemic preconditioning later in adult life by a mechanism involving irreversible fetal reprogramming of protein kinase C epsilon expression (561, 626). A large number of studies have provided evidence that adult animals that were exposed to hypoxia, glucocorticoids or maternal low protein diet or obesity in fetal life demonstrate an increased susceptibility to I/R in the early postnatal period (108a, 211a, 211b, 268a, 268b, 327a, 390a, 491a, 491b, 626, 626a, 626b, 660, 675b, 676a, 782, 863a, 864a, 864b, 864c). These results support the notion that a fetus developing in adverse conditions becomes an adult who is susceptible to enhanced I/R injury.…”
Section: Fetal Programming Transgenerational Inheritance and Suscepmentioning
confidence: 99%
“…With regard to adult susceptibility to I/R after fetal stress, there is a growing body of evidence indicating that reductions in the expression of cardioprotective genes such as protein kinase Cε (PKCε), endothelial nitric oxide synthase (eNOS), adenosine monophosphate (AMP) kinase, and heat-shock protein70 by a ROS-mediated, but nicotinamide adenine dinucleotide phosphate (NADPH) oxidase-independent epigenetic repression mechanism may play a role (211a, 268b, 390a, 491a, 491b, 626, 626a, 626b, 864a). In addition, fetal hypoxia induces changes in extracellular matrix and myofibrillar architecture, oxidative stress, diastolic dysfunction, reduced capillary density, sympathetic dominance, glucocorticoid receptor deficiency, and altered endothelium-dependent vasodilator function in adult hearts, which may contribute to this enhanced susceptibility to I/R (108a, 211b, 268a, 268b, 327a, 327b, 675a, 675b, 675c, 675d, 676a, 857, 863a). …”
Section: Fetal Programming Transgenerational Inheritance and Suscepmentioning
confidence: 99%
“…Protein expression was determined using Western blot, as described previously (Ryan et al 2012). Primary antibodies were PPARa (Cayman Chemicals), PPARg (Santa Cruz), Glut2 (Millipore) and insulin receptor beta (cell signalling).…”
Section: Western Blottingmentioning
confidence: 99%